Sphericity index for bedside diagnosis of acute myocarditis - Antoine AbdelMassih; Sonia El-Saiedi; Rana Hendawy; Reem Esmail; Manal AbdelHameed; Alaa Sobeih; Ahmed Kharabish; Nourine Diab; Hanya Gaber; Nadine El-Husseiny; Hala M. Agha (SpringerOpen, 2023)
Abstract Background Differentiating acute myocarditis (AMY) from dilated cardiomyopathy (DCM) in a patient presenting with acute heart failure and poor systolic function is of utmost importance to initiate timely anti-inflammatory treatment in AMY. Using cardiac magnetic resonance (CMR) or endomyocardial biopsies (EMB) as gold standards might be limited due to the likelihood of hemodynamic compromise. Eccentric myocardial remodeling as measured by sphericity index (SPI) might be useful in differentiating AMY from DCM, due to the progressive increase in transverse LV diameter in DCM. The primary outcome parameter of our study was to test the diagnostic accuracy of SPI in the differentiation of AMY from DCM, while the secondary outcome parameter was to compare the diagnostic accuracy of SPI to troponin I in the same context. For this purpose, we conducted a retrospective study involving a chart review of the files of sixty patients admitted with acute heart failure due to hypokinetic left ventricle in our hospital. Patients were divided after CMR imaging into two groups: group 1 with AMY (n = 30) and group 2 with DCM (n = 30). Demographic and clinical characteristics of the patients, including heart rate, need for mechanical ventilation, use of milrinone, epinephrine and norepinephrine, troponin I, and 2D-derived sphericity index, were collected from patients' files. Results Patients with AMY had a higher need for mechanical ventilation inopressors and vasopressors; 73% of AMY patients required mechanical ventilation and epinephrine use, compared to less than 50% of DCM patients. Troponin I elevation was more marked in AMY compared to DCM patients (0.25 ± 0.04 vs. 0.21 ± 0.03, respectively). SPI was significantly higher in DCM compared to AMY cases, denoting a spherical configuration of the myocardium acquired due to progressive remodeling, because of the chronicity of the pathology. ROC analysis revealed that an SPI ≤ 0.38 was 100% sensitive in differentiating DCM from AMY, compared to a 53% sensitivity with the commonly used troponin I. Conclusion AMY diagnosis can be achieved by the assessment of sphericity index rather than troponin I. The bedside nature and noninvasiveness of SPI should reshape the practice in this context. SPI assessment can be part of point-of-care echocardiography, taught to emergency room (ER) physicians and intensivists.